Política cultural e branquitude: desafios do campo artístico no Ceará - Brandão, Lívio Diego Duarte (2024)
The research analyzes the institutionalized field of art in Ceará in contemporary times, focusing on the validation processes of cultural agents within this field. The study seeks to understand the processes by which an artist is recognized socially and professionally, considering the role of the institutions and agents involved, in addition to investigating the impact of social factors in this process, especially race, but understanding that it is intersected with gender and class. With regard to race, we intend to analyze how the structure of whiteness is mobilized in this validation process. The research proposes questions about the validation criteria imposed by the field of art in Ceará, the role of agents and institutions in this process, and the influence of racial issues in the narratives of agents, even if they are not explicit. To carry out this endeavor, we established dialogues with theorists such as Pierre Bourdieu, Cida Bento, and Antônio Gramsci. Starting from a solid theoretical basis and considering the author's experience as an agent in the field of Ceará art, the research aims to contribute to the understanding of validation mechanisms in the local artistic context, taking into account the dynamics of power, hierarchy and representation in the Ceará art system.